Effect of drying on nutritional and functional quality and electrophoretic pattern of soyflour from sprouted soybean (Glycine max) - Agrahar-Murugkar, Dipika (Springer-Verlag, 2010)
Effect of drying on protein, trypsin inhibitor (TI), nitrogen solubility, water absorption, colour and electrophoretic patterns of flours prepared from germinated soybean varieties ‘JS 9305’ and ‘MAUS 47’ was studied. Drying included sun drying (35–40°C), steaming followed by hot air oven drying at 60°C, hot air oven drying at 100°C and microwave heating at 400 W and 630 W. Sun drying did not reduce the TI to the required 80% and steaming followed by drying and microwave heating affected colour, nitrogen solubility and electrophoretic pattern adversely. Drying at 100°C reduced TI to safe limits and did not adversely affect the nitrogen solubility, colour and electrophoretic patterns and can be recommended for commercial scale drying of germinated soybean to prepare good quality soy flour for product development. Drying at 35–40°C minimally affected the colour, nitrogen solubility and electrophoretic pattern and can be used to prepare soy flour for bakery purposes.